Pemberdayaan Masyarakat dengan Pelatihan Pembuatan Puding Kelor Sebagai Peningkat Kadar Hemoglobin Remaja - Lutfiana Puspita Sari; Anastasia Anastasia; Bundarini Bundarini; Denik Denik; Ermy Ermy; Hafidhatul Hafidhatul; Hartini Hartini; Sri Widiastuti (Jurnal Empathy Pengabdian Kepada Masyarakat, 2022)
Background: The national prevalence of anemia in Indonesia, based on Riskesdas (2018), reached 21.7%. Biologically, every month women experience menstruation. This iron expenditure must be balanced with good nutritional intake. The biggest cause of anemia in women is iron deficiency. About 30% of women in the world experience anemia caused by iron deficiency. Moringa oleifera (Moringa) leaves are a good source of nutrition because they are rich in iron and other vitamins. Because Moringa leaves contain high levels of antioxidants, they are widely used in innovative complementary herbal therapies that benefit health. Methods: Community service activities will be held on August 21–28, 2021, from 08.00–16.00 WIB. The sample for this study was all adolescents in Bedoyo Village, Ponjong Gunungkidul District, totaling 17 teenagers. The community service team conducted a demonstration of making moringa pudding, and representatives of the participants conducted a red demonstration. Participants were given a booklet for making moringa pudding so they could practice at their respective homes for at least 7 days and repeat HB measurements. Evaluation of activities by conducting a pre-test and post-test of Hb levels for all participants. Results: After a demonstration of making Moringa pudding, all participants were able to make it independently by utilizing Moringa leaves in the Bedoyo village environment. The result was an increase in Hb levels before and after consuming Moringa pudding for 7 days, with an average increase in Hb levels of 2.8 g/%. Conclusion: Pudding kelor can effectively increase hemoglobin levels in adolescents.